Kadar Gula Darah Dan Gambaran Histopatologi Pankreas Tikus Putih (Rattus norvegicus L.) Hiperglikemia Setelah Pemberian Ekstrak Etanol Jenggot Musa (Tillandsia usneoides L.) - Isma Kurniatanty; Yuniati Wadhihah (Departmet of Biology, Universitas Islam Negeri Sunan Kalijaga, 2022)
Diabetes mellitus is a disease characterized by hyperglycemia due to the destruction of pancreatic cells as insulin-producing cells. Natural ingredients from plants are an alternative for diabetes treatment, one of which is beard musa (Tillandsia usneoides L.). Beard musa is a plant that has bioactive compounds in the form of flavonoids that have the potential to help control blood sugar levels. This study aims to determine the effect of beard musa ethanol extract on reducing blood sugar levels and histopathological description of the pancreas of white rats (Rattus norvegicus) induced by alloxan. The study was divided into five treatment groups, namely positive control, negative control, dose I (dose of 125 mg/kg BW), dose II (dose of 250 mg/kg BW), and dose III (dose of 500 mg/kg BW). The test animals used were white rats weighing 150-300 grams which were acclimatized for 7 days. After that, the test animals were induced with alloxan for 7 days before treatment to determine the hyperglycemic effect. The treatment in each group was carried out for 14 days in which negative control was given aquadest, positive control was given glibenclamide, and doses I, II and III were given beard musa extract with 4 times of blood collection, namely days 0, 7, 14, and 21. Then the phytochemical screening was carried out with the flavonoid test and the alkaloid test. On day 21, mice were sacrificed to make histological preparations. The results showed that the three doses of beard musa ethanol extract were able to reduce blood glucose levels in hyperglycemic rats, where a dose of 250 mg/kg BW was more capable of providing a hypoglycemic (antidiabetic) effect to normal blood sugar levels in hyperglycemic white rats with successive decreases during 14 days compared to other doses. While the ethanol extract of beard musa at all doses did not affect the structure of the pancreatic cells of hyperglycemic white rats.